2006
DOI: 10.1029/2005gl025124
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic simulations of x‐line expansion in 3D reconnection

Abstract: The dynamics of x‐line formation and evolution in 3D magnetic reconnection is studied using a fully kinetic approach. An x‐line of small length is initialized using a perturbation localized in the current direction. The electrons and ions drift diamagnetically along the current direction of the initial x‐line and are further accelerated by the reconnection electric field. The electron and ion motion is in opposite directions and each species extends one end of the x‐line. Several predictions based on this pict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
54
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(62 citation statements)
references
References 20 publications
6
54
2
Order By: Relevance
“…While the pressure tensor-based thermal dissipation persists, it supplies only approximately half of the force-balance if the plasma is relativistic enough. This is a deviation from nonrelativistic results, 2,[8][9][10] which show a strong dominance of the thermal dissipation mechanism.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…While the pressure tensor-based thermal dissipation persists, it supplies only approximately half of the force-balance if the plasma is relativistic enough. This is a deviation from nonrelativistic results, 2,[8][9][10] which show a strong dominance of the thermal dissipation mechanism.…”
Section: Discussioncontrasting
confidence: 71%
“…2 Although some questions remain in turbulent plasmas, most recent investigations have found that, in the central magnetic reconnection region, the relevant additional term is provided by the thermal inertia. [2][3][4][5][6][7][8][9][10] The physics behind this is associated with the transient nature of particle orbits in the reconnection region. Pre-acceleration particles are continuously transported into the reconnection region, whereas accelerated particles tend to leave.…”
Section: Introductionmentioning
confidence: 99%
“…This scenario is supported by a number of kinetic models, [9][10][11][12]15 but others also show turbulence in the inner reconnection region. [16][17][18] Limitations of this theory may also be found in relativistic plasmas, or for very strong guide fields, where the Larmor radius becomes comparable to the Debye scale. Therefore, the generality of the thermal inertia-based process is still to be determined, but it seems likely that it will apply in a large variety of situations.…”
Section: Discussionmentioning
confidence: 99%
“…This region has been observed extensively at the ion-scale [3][4][5][6][7][8][9], but little is know at electron skin depth (λ e ) scales. This region also has been examined extensively with numerical simulations and analytic analysis [10][11][12][13][14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%